2020
DOI: 10.1111/izy.12269
|View full text |Cite
|
Sign up to set email alerts
|

Survey to identify factors affecting breeding of Wolverines Gulo gulo within the EEP

Abstract: Conservation biologists have long faced the challenging task of large-carnivore conservation. The hunting habits and specific ecology of these species make their conservation difficult and Wolverines Gulo gulo are no exception. Wolverines are close to extinction as a result of human persecution and habitat loss. The European Association of Zoos and Aquaria (EAZA) introduced the European Endangered Species Programme (EEP) for the Wolverine in 1994 but only irregular breeding has been achieved. The aim of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…A survey of Japanese zoos found only a little over half of interviewed zoos conducted daily training with their red pandas [128]. Similar results have been found in surveys of other species and in other regions; a survey of wolverines (Gulo gulo) in Europe, for example, found that only 57% of respondents trained their animals [129]. Training for all animals should be considered, including making the time for such interactions to occur on a daily, weekly, and monthly basis.…”
Section: Small Mammalssupporting
confidence: 58%
“…A survey of Japanese zoos found only a little over half of interviewed zoos conducted daily training with their red pandas [128]. Similar results have been found in surveys of other species and in other regions; a survey of wolverines (Gulo gulo) in Europe, for example, found that only 57% of respondents trained their animals [129]. Training for all animals should be considered, including making the time for such interactions to occur on a daily, weekly, and monthly basis.…”
Section: Small Mammalssupporting
confidence: 58%
“…There are EEPs and SSPs for four small carnivore species; Binturong (VU), Fosa (VU), Giant otter Pteronura brasiliensis (EN) and Red panda (EN). The EAZA Small Carnivore Taxon Advisory Group (TAG) has also established EEPs for Bokiboky Mungotictis decemlineata (EN), Owston's palm civet Chrotogale owstoni (EN) (Willcox et al ., 2020), Ring‐tailed vontsira Galidia elegans (LC) and Wolverine Gulo gulo (LC; although in 2018 the species was Red Listed as VU in Europe: see https://www.iucnredlist.org/species/9561/144336120) (Loberg et al ., 2020), among others. The AZA Small Carnivore TAG has established several SSPs, including for Black‐footed ferret (EN) and Asian small‐clawed otters (VU).…”
Section: Figmentioning
confidence: 99%
“…Many species are obscure and little studied, often because of their size, and elusive and nocturnal habits. Zoo studies, such as those on behaviour, not only help us to understand housing requirements and the impact of visitors, but also provide a basis to our understanding of their behaviour in the wild (Amaral & Rosas, 2020; Bourgeois et al ., 2020; Kappelhof & Weerman, 2020; Loberg et al ., 2020; Rossi et al ., 2020; Schikora, 2020; Willcox et al ., 2020). Early studies on otters in captivity by the author (N.D.) provided a knowledge base and facilitated later studies in the wild (Duplaix, 1980).…”
Section: Figmentioning
confidence: 99%